Self-Awareness Of Persons With Disabilities To Carry Out Rehabilitation, Increasing Participation And Rehabilitation Needs - Yopi Harwinanda Ardesa (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: Rehabilitation of persons with disabilities increases productivity. Self-awareness motivates participation in rehabilitation. This study aims to analyze the relationship between self-awareness and rehabilitation. Methods: This research is a quantitative descriptive study with a cross sectional approach with a population of people with disabilities in Colomadu District, Karanganyar. Sampling using purposive sampling technique with the inclusion criteria of persons with physical disabilities as many as 23 subjects. The research instrument used a questionnaire. Data collection was carried out in December 2019. The data analysis technique used the non-parametric Rank Correlation test Spearman test. Results: The results of data analysis showed that self-awareness was not related to the rehabilitation of persons with physical disabilities with a value of r = 0.108, (p>0.05). The adjustment value (R2) is 0.118, meaning that 11.8% of individual autonomy variations can be explained by variations in self-awareness. While 88.2% was caused by other factors. Self-awareness does not improve rehabilitation implementation. Conclusion: External supporting factors are needed to increase the participation of persons with disabilities and self-awareness as internal motivation to strengthen external supporting factors in the implementation of rehabilitation.